Use of fertility services in Australian lesbian, bisexual and queer women's pathways to parenthood. (18th May 2020) - Power, Jennifer; Dempsey, Deborah; Kelly, Fiona; Lau, Melanie
Abstract : Background: It is estimated that up to one in three lesbian, bisexual or queer (LBQ) women in Australia have children. In the past decade, it has become common for LBQ women to pursue pregnancy using clinic‐acquired donor sperm. Aims: The aims of this paper are to explore pathways to parenthood among Australian LBQ women in the context of increased access to fertility clinics and identify the type of clinical fertility services being used. Materials and method: This paper reports on female LBQ parents and expectant/prospective parents who participated in a 2016/2017 online survey of Australian lesbian, gay, bisexual, transgender and queer (LGBTQ) adults exploring reproductive choices, pathways to parenthood, conception method and use of clinical fertility services. Results: More than half the children reported on by current parents (52%) had been conceived using clinical fertility services. When asked what factors influenced a parent respondent's decision to use fertility services: 80% indicated access to donor sperm, 41% indicated fertility problems. Of respondents who had accessed donor sperm, over half (57%) had used in vitro fertilisation (IVF) services. Conclusions: These findings indicate that use of fertility clinics to access donor sperm is common for LBQ women, including those with no known fertility problems, and that most women who access donor sperm conceive using IVF rather than intrauterine insemination. More needs to be known about the context and reasons for this, including factors that influence LBQ women's decision making on their pathway to parenthood.